QUALITATIVE STUDY OF THE CHALLENGES AND STRATEGIES OF HISTORY TEACHERS AT SMAN 2 MEDAN IN IMPLEMENTING THE INDEPENDENT CURRICULUM - Sidauruk, Delvi; Nugraha, Muhammad Adika; Aisyah, Sitti (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to explore the challenges faced and the strategies used by history teachers at SMA Negeri 2 Medan in implementing the Independent Learning Curriculum. Qualitative research methods were used to collect data through in-depth interviews with eight experienced history teachers. Data analysis was carried out using a thematic approach to identify general patterns in the challenges faced and strategies implemented. The research results show that history teachers face a variety of challenges in implementing the Merdeka Belajar Curriculum, including a lack of resources, the need for additional training, and pressure to balance the curriculum. To overcome these challenges, teachers use a variety of strategies, including collaboration between teachers, integration of technology, and adjustments in teaching. The implications of these findings for developing teacher professionalism and improving the implementation of the Independent Learning Curriculum are discussed in the context of this research. The challenges of implementing the Independent Learning Curriculum, including limited resources, the need for additional training, and the pressure to balance the existing curriculum with new principles, are the main obstacles for history teachers. History teachers use various strategies, such as collaboration between teachers, integration of technology in learning, and adjustments in teaching, to overcome challenges and increase the effectiveness of history teaching. The implications of these findings include the need to provide adequate resources, collaborative support from various parties, and increase the integration of technology in history learning. By understanding and overcoming the challenges faced by history teachers, as well as implementing appropriate strategies, the implementation of the Independent Learning Curriculum at SMA Negeri 2 Medan can be improved, which in turn will bring benefits to the development of teacher professionalism and improve the quality of learning in the school. Therefore, concrete steps need to be designed and implemented to support history teachers in facing challenges and improving the implementation of the Independent Learning Curriculum at SMA Negeri 2 Medan.